2020
DOI: 10.1128/mbio.03020-19
|View full text |Cite
|
Sign up to set email alerts
|

Scratching the Surface: Bacterial Cell Envelopes at the Nanoscale

Abstract: The bacterial cell envelope is essential for viability, the environmental gatekeeper and first line of defense against external stresses. For most bacteria, the envelope biosynthesis is also the site of action of some of the most important groups of antibiotics. It is a complex, often multicomponent structure, able to withstand the internally generated turgor pressure. Thus, elucidating the architecture and dynamics of the cell envelope is important, to unravel not only the complexities of cell morphology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…Quantitative rupture force measurement with AFM is a promising way to characterize how the lipopeptide affects the mechanical properties of the bacterial surface. The AFM probe as nanoindentation depth plots was used and analyzed according to theoretical models for providing quantitative information on the rupture force of the sample [ 20 ]. These models have been applied toward bacteria, E. coli HB101.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative rupture force measurement with AFM is a promising way to characterize how the lipopeptide affects the mechanical properties of the bacterial surface. The AFM probe as nanoindentation depth plots was used and analyzed according to theoretical models for providing quantitative information on the rupture force of the sample [ 20 ]. These models have been applied toward bacteria, E. coli HB101.…”
Section: Resultsmentioning
confidence: 99%
“…The organization at the nanoscale of the bacterial cell wall was examined using functionalized AFM tips to address changes in cell morphology, surface roughness, and elasticity after antibiotic treatment. The high resolution and sensitivity of AFM have brought novelties into the real-time effects of antibiotics and external agents in the cell envelope ultrastructure [ 20 ]. Fantner et al developed special AFM cantilevers allowing high-speed tapping-mode AFM, and they observed the kinetics of antimicrobial peptide CM15 degrading individual E. coli cells at high resolution in real time at the nanometer level [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of atomic force microscopy (AFM) paved the way for the investigation of the properties and behaviour of bacterial surfaces under conditions that are much closer to those relevant to antibiotic action in vivo [36]. AFM has demonstrated the potential to monitor real-time effects of antimicrobials on the surfaces of living bacterial cells under native conditions [37,38] and can achieve sub-second time resolution, enabling single molecule tracking on the bacterial surface [39].…”
Section: Methods To Investigate Antibiotics Effect On the Native Bacterial Surfacementioning
confidence: 99%
“…High resolution topographic imaging studies of healthy bacteria have shown that the cell surface may vary considerably based on whether a species is Gram-positive or Gram-negative as well as on the presence or absence of surface molecules such as cell wall polysaccharides or S-layers (Viljoen, Foster, Fantner, Hobbs, & Dufrêne, 2020). In Gram-negatives and mycobacteria that have outer membranes masking the peptidoglycan (PG) layer, the cell surfaces are often relatively featureless and smooth (Alsteens et al, 2008;Mathelié-Guinlet, Asmar, Collet, & Dufrêne, 2020;Vassen et al, 2019).…”
Section: Seeing the Invisiblementioning
confidence: 99%